PERANCANGAN SISTEM ASESMEN LITERASI INFORMASI BERBASIS WEB - -, Rachmawati; Muljono, Pudji; Sitanggang, Imas Sukaesih (Edulib, 2017)
Abstract, Information literacy is an important skills for 21st century learners. One of methods to evaluate the implementation of information literacy program in school library is assessment of information literacy competence. The objectives of this research were to establish a standard of information literacy for Indonesian students and to design a webbasedinformation literacy assessment system. This research employed Delphi technique with two rounds questionnaire distributed among panelists of 9 experts. The experts consists of three school librarians, two teachers and four information literacy researchers. Six standards and 40 performance indicators were identified as information literacy standard. The design ofsystem resulted models which presented in System Flowchart, Data Flow Diagram and Entity-Relationship Diagram.Keywords: competency standard, information literacy assessment, web-based system